Effects of replacing fish oil with microalgae biomass (Schizochytrium spp) as a source of n-3 LC-PUFA to Atlantic salmon (Salmo salar) on growth performance, fillet quality and fatty acid composition - Mizambwa, Hellen Edward (Norwegian University of Life Sciences, Ås, 2017)
Low levels of EFA in fish feed as a result of changes in diet composition brings a need of finding a novel ingredient that will supplement Essential Fatty Acids (EFA) in fish feed. Microalgae have ability of producing omega-3 polyunsaturated fatty acids (PUFA) and for that are predicted to be a reliable feed ingredients in replacing fish oil in the near future. Main objective of present study was to evaluate effects of replacing fish oil (FO) with microalgae biomass (Schizochytrium spp.) (AA) as a source of n-3 LC-PUFA to Atlantic salmon (Salmo salar) on growth performance, fillet quality and fatty acid composition. Atlantic salmon were fed two diets: FO control diet and AA enriched diet for 400 days. Fish that were fed AA diet showed higher final weight, specific growth rate (SGR) and condition factor (K) than fish fed the FO control diet. Fillet quality was good and analysis showed no significant difference between fish in the two dietary group on gaping score, fillet yield and redness. Although a significant difference was noted on fillet yellowness in fish from AA dietary group. Furthermore, Folch method was used to analyse total fat content in liver and fillet. Statistical analysis showed no significant difference in fat content between the two dietary groups. Fatty acid composition was also analysed by using gas chromatography (GC) method. Liver and muscle fatty acid compositions varied between the two dietary groups. Percentage of eicosapentaenoic acid (EPA) was lower and the percentage of docosahexaenoic acid (DHA) was higher in AA dietary group fish than in fish from FO dietary group. Generally, results from our study shows that inclusion of (Schizochytrium spp) biomass (6.25% of the diet) as source of DHA is able to improve final weight, SGR, K, deposition of DHA in tissues (fillet and liver) without reducing the quality of fillet in terms of red color and gaping score. NOFIMA-ÅS M-FT